Parenting and Subtypes of Aggression: Exploring the Relationship between Parenting Strategies and Subtypes of Aggression (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Less research has been conducted on the etiological factors of the different types of aggression there are few findings regarding the particular parenting strategies associated with proactive and reactive aggression mainly. Dodge (1991) has hypothesized that reactive aggression has its roots in early childhood, and that rejection and that rejection and maltreatment by parents will be associated with such behaviour. Dodge also hypothesized greater attachment disruption in reactive rather than proactively aggressive children, but research so far only demonstrates a link between insecure attachment and both types of aggressive behaviour (Marcus Kramer, 2001).